Development of Semi-burning sweet potato automorphing machine - Chang, Hui IL (International Journal of Advanced Science and Technology, 2019)
Background/Objectives: The objective if this study is to develop a product with variously modifying knife-replacing structures for cutting machine that automatically truncates and creates semi-arid sweet potato.Methods/Statistical analysis: Developed product is designed to perform with a press method reducing the number of added devices and efficiently utilize production space through evaluation of performance on standby power of sweet potato cutting machine and reaction time on emergency stoppage as well as hardness of a blade.Findings: It is possible only to cut sweet potato in unified shape with existing production method. However, it is possible to make sweet potato in various shapes by completing the manufacturing of replaceable blade cover and also to develop new products by cutting and processing fruits and vegetables other than sweet potato in the future with blade replacing method of developed product. Improvements/Applications: It is possible to develop new products as it becomes feasible to process new items with the development of relevant product over currently producing sweet potato-processing products.